The seat fortress of Suceava (Confluenţe Bibliologice, 2023)
The article presents the history of the Seat Fortress in Suceava, which remained a living testimony of a glorious and turbulent past of the Principality of Moldova. The rulers (Petru I Mușat, Ştefan cel Mare, Bogdan al III-lea and Ștefăniță Vodă, Alexandru Lăpușneanu, Vasile Lupu) who contributed to the construction of this historical monument are mentioned.
Keywords: rulers; Romanian history